Nothofagus and the associated palynoflora from the Late Cretaceous of Vega Island, Antarctic Peninsula - Romero, Edgardo Juan; Rodriguez Amenabar, Cecilia; Zamaloa, María C.; Concheyro, Graciela
Nothofagaceae fossil leaves and an associated palynoflora from Late Cretaceous sediments of Vega Island, eastern Antarctic Peninsula, are presented. The leaves are described as Nothofagus sp. 1 and Morphotype LDB 1, and come from the Snow Hill Island (late Campanian-early Maastrichtian) and the López de Bertodano (late Maastrichtian) formations, respectively. The palynoflora obtained from levels immediately above and below the Nothofagus sp. 1 and in the same horizon as the Morphotype LDB 1, included terrestrial and marine elements. In the palynoflora associated with Nothofagus sp. 1, conifers are dominant and pollen grains with Nothofagus affinity are represented by four species: Nothofagidites kaitangataensis (Te Punga) Romero 1973 and Nothofagidites senectus Dettmann and Playford 1968 which belong to the ancestral pollen type, as well as Nothofagidites dorotensis Romero 1973 and Nothofagidites sp. of the brassii-type. Cryptogamic spores, marine dinoflagellate cysts and algae, among others, are part of the assemblage. The palynoflora associated with the Morphotype LDB 1 also contains abundant conifer and angiosperm pollen grains with N. dorotensis as the only Nothofagus species recorded. Marine dinoflagellate cysts are scarce while fungi and phytodebris are common elements. The joint presence of marine and non-marine palynomorphs supports a probable nearshore environment at time of deposition for both units. Pollen and spore evidence suggests a mixed conifer and angiosperm forest, with Podocarpaceae and Nothofagus as the main components, and fern, lycopods, and mosses in the understory. This forest developed under temperate and moist conditions during the middle Campanian-Maastrichtian. Fil: Romero, Edgardo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Rodriguez Amenabar, Cecilia. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. ...